Greedy mouth - Potter, Jennifer ([London] : Arts & Commerce, 1998)
"Welcome to the world of Greedy Mouth, the story of Jessie - first generation kid from Las Vegas ... and her subsequent escape from TV addiction, nuclear contamination, cheerleading, and microwave fast food."--Cover.
Keywords: Las Vegas (Nevada) -- Fiction; Action and adventure fiction